2004
DOI: 10.1115/1.1949621
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Single-Phase AC and Multiphase DC Resistance Spot Welding

Abstract: This paper presents a comparative study of the AC and MFDC resistance spot welding process. Both experiments and finite element simulation were conducted to compare the weld size and energy consumption. The experiments were performed on two identical spot welding machines, one with a single phase ac and the other with a mid-frequency DC weld control. The machines were instrumented such that both the primary and secondary voltage and current signals could be collected for energy calculation. The finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Temperature-dependent material properties and contact properties [7,8,18] were used. The BCs and the material properties were the same for the sinusoidal current input and RMS current input except for the current inputs, i.e., the RMS current input used the setting value I w of welding machine, and the sinusoidal current input used w 2 sin(2π ).…”
Section: Calculation Modelmentioning
confidence: 99%
“…Temperature-dependent material properties and contact properties [7,8,18] were used. The BCs and the material properties were the same for the sinusoidal current input and RMS current input except for the current inputs, i.e., the RMS current input used the setting value I w of welding machine, and the sinusoidal current input used w 2 sin(2π ).…”
Section: Calculation Modelmentioning
confidence: 99%
“…Some researchers have investigated the cause of vibration during a welding process [7] found that there are mechanical vibrations and high current peaks when using alternate current, and the vibrations disappear when using direct current. It indicated that mechanical vibrations are generated by the alternating welding current.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the amount of thermal expansion, melting, and expulsion can be corrected to the slope and magnitude of the displacement curve. A number of control systems have been developed based on maximum electrode displacement or its changing rates [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance spot welding systems described in different realizations [2]- [5], are widely used in the automotive industry. Although the alternating or direct currents (dc) can be used for welding, this work focuses on the RSWS (Fig.…”
Section: Introductionmentioning
confidence: 99%